2016
DOI: 10.1200/jco.2016.34.15_suppl.e12512
|View full text |Cite
|
Sign up to set email alerts
|

Value of breast cancer molecular subtypes and Ki67 expression for the prediction of efficacy and prognosis of neoadjuvant chemotherapy in a Chinese population.

Abstract: The aim of the study was to determine the predictive role of breast cancer subtypes in the efficacy and prognosis of neoadjuvant chemotherapy (NCT) regimens combining taxanes and anthracyclines. Data from 240 patients with breast cancer who received surgery after 4 to 6 weeks of NCT were retrospectively analyzed. The patients were classified into luminal A, luminal B, HER2 overexpression, and triple negative breast cancer (TNBC) as well as low Ki67 (14%) and high Ki67 (> 14%) expression groups using immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition, the expression of KI-67 and prognosis were closely related to pTNM stage and PR expression [13]. It is indicated that Ki-67 positive can lead to higher histological grade of BC, Wang J et al showed that it is bene cial for Ki-67 expression < 40%, which can signi cantly increase DFS in BC patients [14]. However, HER2 overexpression can lead to invasive breast cancer, which overexpression was negatively correlated with the expression of PR and ER.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of KI-67 and prognosis were closely related to pTNM stage and PR expression [13]. It is indicated that Ki-67 positive can lead to higher histological grade of BC, Wang J et al showed that it is bene cial for Ki-67 expression < 40%, which can signi cantly increase DFS in BC patients [14]. However, HER2 overexpression can lead to invasive breast cancer, which overexpression was negatively correlated with the expression of PR and ER.…”
Section: Introductionmentioning
confidence: 99%